Study on the operational characteristics of the vanadium redox flow battery - Roch, Edward Reuben. (2013)
The Vanadium Redox Flow Battery (VRFB) holds significant promise in the storage of energy systems with great capabilities and potential with the applications in an array of concepts. The vanadium battery technology holds the answer for the future’s search for clean and renewable source of energy.